Exploring the Spatial–Temporal Variation in Cultivated Land Quality and Influential Factors in the Lower Reaches of the Yangtze River from 2017 to 2020 - Zixuan Wang; Xufeng Fei; Meiling Sheng; Rui Xiao (Land, 2023)
Cultivated land quality is directly related to national food security; hence, it is necessary to determine the spatial–temporal characteristics and factors that influence its variation. This study analyzed the soil properties and cultivated land quality in the Hang-Jia-Hu Plain, the most important grain production base in Zhejiang Province, located in the lower reaches of the Yangtze River, from 2017 to 2020. In addition, the factors that influenced cultivated land quality variation were explored. The results showed that soil pH and soil organic matter (SOM) significantly improved from 6.32 and 29.07 g/kg in 2017 to 6.38 and 31.54 g/kg in 2020, whereas the variations in available phosphorus (AP) and available potassium (AK) were not significant. More than 60% of the cultivated land still had the potential for soil nutrient status improvement. The cultivated land quality indicator (CLQI) calculated based on the national standard (GB/T 33469-2016) significantly increased from 0.90 in 2017 to 0.91 in 2020. According to the CLQI classification, approximately three quarters of the cultivated land was defined as high-yielding fields. Although the spatial pattern for CLQI was similar between 2017 and 2020, more than 75% of the cultivated land quality showed an increasing trend that was mainly located in the northeastern and central areas. The results of influential factor detection indicated that the improvement in SOM and available soil nutrients including AP and AK was the main reason for the CLQI increase, whereas the climate, topography, and socioeconomic factors had little influence on the change in CLQI. In addition, when influential factors interacted, a significant increase in the explanatory ability for CLQI was obtained, especially for the interaction of SOM and AP variation, which explained 41% of the CLQI variation. This study provides basic foundations and references for cultivated land quality monitoring and improvement in the lower reaches of the Yangtze River, China.